Determining the rate of mother-to-child human immunodeficiency virus transmission among pregnant women in An Giang province - Tran, Quang Hien (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Determining the rate of pregnant women infected with human immunodeficiency (HIV) is one of the important factors for planning HIV prevention policies. This study aims to determine the rate of HIV infection among pregnant women in An Giang province in 2010. Methods: This is an epidemiological investigation study with analysis. The subjects are all pregnant women who are from An Giang and reside in An Giang province. They came for prenatal check-ups and gave birth at all medical facilities in communes, districts, and the province of An Giang from 01 January 2010 to 31 December 2010. Results: The rate of pregnant women infected with HIV in An Giang province is 0.29%, which is at an average level compared to the whole country. The occupation of pregnant women is related to HIV infection; compared to the occupation of civil servants, the occupation of trading has an 18.7 times higher risk of HIV infection (RR=18.7, p<0.01); the occupation of laborer has a 13 times higher risk (p<0.05); the occupation of farmer has a 6.3 times higher risk (p<0.05); the occupation of Housewife has a 4 times higher risk (p<0.05). Conclusions: The rate of pregnant women infected with HIV in An Giang province in 2010 was 0.29%. The occupational factor of pregnant women shows a correlation with HIV infection.